LEARNING QIRA'AH AL-QUR'AN USING THE TILAWATI MOBILE APPLICATION IN THE DIGITAL ERA - Padriyanti; Zakir, Supratman; Akbar, Muh. Ali; Hilmi, Moh.; Yakin, Lalu Nurul (Prodi Pendidikan Agama Islam STAI Darul Falah, 2024)
The aim of this research is to describe learning Qira'ah Al-Qusr'an using the Tilawati Mobile application in the digital era. This application is designed to facilitate interactive learning of recitation of Al-Qur'an by using modern features such as voice recording, real-time evaluation, qori and mutual options, and visualization of recitation. The main aim of this application is to improve and assist the users’ Al-Qur'an reading skills with greater accuracy and fluency while increasing understanding of the rules of recitation and the context of the meaning contained in the Quran. This research employed library research as it is applicable with the aim of this research. The research procedures covered documents the implementation of technology in Islamic religious education, explores user responses to this digital innovation, and elaborates its impact on the understanding and development of qira'ah competencies. By integrating technology into religious learning, the Tilawati Mobile application acts as an effective tool in facilitating holistic learning of Al-Qur’an in the digital era.